Income Shocks and Corruption in Africa : Does a Virtuous Cycle Exist? - Voors, Maarten J.; Bulte, Erwin H.; Damania, Richard (2012)
Empirical evidence suggests that governance quality is a key driver of economic growth and that, in turn, higher incomes might have a positive causal effect on the quality of governance. Such complementarity could invite virtuous cycles of development. Using a measure of corruption as our proxy for the quality of governance, and rainfall as an instrument for income, we explore this issue and find evidence to the contrary. For a panel of African countries, positive income shocks on average tend to invite extra corruption. Closer inspection, however, reveals that this result can be attributed to the most corrupt countries. Conversely, countries with a sufficiently low level of corruption can escape the detrimental effect of income booms on corruption and may actually experience a virtuous cycle of development.